Sosialisasi Implementasi Motivasi Kebutuhan Masa Kanak-Kanak Akhir bagi Guru Sekolah Dasar - Miranti Widi Andriani; Khoirul Anwar (IKIP PGRI Bojonegoro, 2021)
Current teacher’s problems include the need to increase knowledge and skills in strengthening the theory of application of motivational needs in late childhood. The Purpose of this service activity are 1) to help elementary school teachers understand Abraham Maslow's theory of motivational needs, 2) to strengthen the application of Abraham Maslow's theory of motivational needs in late childhood. The participants of the activity were elementary school teachers at SDN Pejagan 7 Bangkalan and teachers to be who volunteered at elementary schools totaling 47 participants. The activity method is carried out by socializing in the network (online) using the Zoom Meeting application. Training activities include web meetings, discussions, consultations, and mentoring. This service activity has been able to encourage teachers to implement the theory of motivational needs in elementary school age students where the teacher teaches. Keywords: socialization online, need motivation, late childhood ABSTRAKPermasalahan guru saat ini diantaranya adalah perlunya meningkatkan pengetahuan dan keterampilan dalam pemantapan teori aplikasi motivasi kebutuhan pada masa kanak-kanak akhir. Tujuan kegiatan pengabdian ini adalah 1) membantu guru sekolah dasar memahami teori motivasi kebutuhan Abraham Maslow, 2) pemantapan pengaplikasian teori motivasi kebutuhan Abraham Maslow pada usia kanak-kanak akhir. Peserta kegiatan adalah guru sekolah dasar di SDN Pejagan 7 Bangkalan dan calon guru yang menjadi sukarelawan di sekolah dasar berjumlah 47 peserta. Metode kegiatan dilakukan dengan sosialisasi dalam jaringan (daring) menggunakan aplikasi zoom meeting. Kegiatan pelatihan meliputi web meeting, diskusi, konsultasi, dan pendampingan. Kegiatan pengabdian ini telah mampu mendorong guru untuk mengimplementasikan teori motivasi kebutuhan pada anak didik usia sekolah dasar tempat guru mengajar. Kata Kunci: sosialisasi daring, motivasi kebutuhan, masa kanak-kanak akhir